Evaluating episodic hydrothermal activity in South China during the early Cambrian: Implications for biotic evolution. (July 2020) - Wang, Zhanghu; Tan, Jingqiang; Boyle, Richard; Hilton, Jason; Ma, Zhongliang; Wang, Wenhui; Lyu, Qiao; Kang, Xun; Luo, Wenbin
Abstract: The early Cambrian (541–514 Ma) was a crucial interval for the evolution of life on Earth, popularly known as the "Cambrian Explosion". Here, we report the timing of changes in hydrothermal and depositional inputs, as well as paleo-redox state, which may have influenced biogeochemical changes. According to high-resolution petrology, fossil distributions, isotopic records, and inorganic geochemistry, the lower Cambrian of the South China can be subdivided into four intervals: the lowermost Cambrian Zhujiaqing Formation (Cam-I); the Cambrian Stage 2 Shiyantou Formation (Cam-II); the lower part of the Cambrian Stage 3 Yu'anshan Formation (Cam-III); and the mid–upper Cambrian Stage 3 and the middle–upper part of the Yu'anshan Formation, continuing into the Canglangpu Formation (Cam-IV). Hydrothermal events are detected during the early Cam-I, Cam-II, and Cam-III intervals. During the early Cam-I and Cam-II intervals, these events coincided with extensive bottom water euxinia, which in turn may have restricted the spread or proliferation of Ediacaran fauna and small shelly fauna. Through the whole Cam-III interval, further hydrothermal events occurred concurrently with euxinic and ferruginous conditions, probably within a single spatially stratified water column, again plausibly restricting the spread of aerobic organisms. In conjunction with the cessation of hydrothermal events and the gradual lowering of sea level during the late Cam-III, oxic water environments gradually spread into relatively deep-water regions, concurrent with the emergence of the Chengjiang and Qingjiang faunas. These data suggest that periodic hydrothermal events may have had a significant impact on the spread, radiation and extinction of macroscopic fauna during the early Cambrian in South China. Graphical abstract: Image 1 Highlights: 18 South-Chinese lower Cambrian sections were investigated. Petrographic/geochemical data revealed stratigraphic correlation and redox state. Episodic hydrothermal intervals promoted anoxia during Cambrian stages I-II Decline in hydrothermal input by stage IV coincided with oxic conditions. Hydrothermal decline (increase) coincides with biotic diversification (extinction).